2022
DOI: 10.1242/jcs.258796
|View full text |Cite
|
Sign up to set email alerts
|

CPVT-associated calmodulin variants N53I and A102V dysregulate Ca2+ signalling via different mechanisms

Abstract: Catecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited condition that can cause fatal cardiac arrhythmia. Human mutations in the Ca2+ sensor calmodulin (CaM) have been associated with CPVT susceptibility, suggesting that CaM dysfunction is a key driver of the disease. However, the detailed molecular mechanism remains unclear. Focusing on the interaction with the cardiac ryanodine receptor (RyR2), we determined the effect of CPVT-associated variants N53I and A102V on the structural charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 91 publications
0
11
0
Order By: Relevance
“…However, another research group showed a decreased activation of CaMKII in the presence of CaM variants N97S, D95V, and D129G ( 78 ). We previously investigated CPVT-associated CaM variants and showed that CaM-N53I did not affect the kinase activity of CaMKIIδ, whereas CaM-A102V significantly increased substrate phosphorylation levels by ∼60% ( 79 ). Interestingly, autophosphorylation levels between CaM-WT and CPVT-associated mutants were not significantly different, demonstrating that the increase in kinase activity observed for CaM-A102V cannot be attributed to enhanced autophosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, another research group showed a decreased activation of CaMKII in the presence of CaM variants N97S, D95V, and D129G ( 78 ). We previously investigated CPVT-associated CaM variants and showed that CaM-N53I did not affect the kinase activity of CaMKIIδ, whereas CaM-A102V significantly increased substrate phosphorylation levels by ∼60% ( 79 ). Interestingly, autophosphorylation levels between CaM-WT and CPVT-associated mutants were not significantly different, demonstrating that the increase in kinase activity observed for CaM-A102V cannot be attributed to enhanced autophosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…For the biophysical experiments, recombinant protein was obtained by cloning the human CaM gene into pE-SUMOPro as previously described ( 79 ). CaM variant E140G was generated by site-directed mutagenesis following the QuikChange protocol (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For biophysical and structural biology experiments. The sequence of human wild-type (WT) CaM was subcloned into the pE-SUMOPro-Kan vector (LifeSensors, USA) as previously described (Prakash et al, 2021(Prakash et al, , 2023. A series of site-directed mutagenesis (SDM) reactions were performed using the QuikChangeII kit (Agilent Technologies, USA), according to the manufacturer's recommendation, in order to generate LQTS-associated CaM mutants D95V, N97I and D131H.…”
Section: Molecular Biologymentioning
confidence: 99%
“…The non-cardiac cell line human embryonic kidney 293 is used in cardiac research to explore the effect pathogenic variants have on the activity of specific ion channels. Pathogenic variants of ion channel genes can be transiently expressed in the cells to elucidate cellular mechanisms behind cardiac disease (Prakash et al, 2021). The reader is directed to Odening et al (2021) for a more detailed description on the role such cells play in cardiac electrophysiology research.…”
Section: Cellular Systems: Immortalised Cardiac Cellsmentioning
confidence: 99%